Les simulateurs informatiques, ressources pour la formation des enseignants de mathématiques - Emprin, Fabien; Sabra, Hussein (Canadian Journal of Science, Mathematics and Technology Education, 2019)
In this paper, we analyze the criteria used to design a computer simulator for learning mathematics in the classroom. Although simulators are used in many professional fields to minimize risk and accelerate the process of gaining experience, few simulators are available for the purposes of teacher training. Therein we see an opportunity to introduce the use of a simulator into the confines of in-class training and, in so doing, facilitate interactions between theory and practice. To determine the design criteria for the simulator, we look at the benefits and risks of using technologies for training purposes as well as two theoretical frameworks that help us characterize technology-based teaching practices. We continue by showing how these criteria factored into the design of our in-class computer simulator. Finally, we discuss the possibilities for the development of other software programs.
Keywords: formation des enseignants; pratiques enseignantes; simulateur; usages des technologies numériques